Hemodynamic Monitoring in the Critically Ill Patient – Current Status and Perspective - Sakka, Samir G. (Frontiers in Medicine, 2015)
In the critically ill patient, early and effective hemodynamic management including fluid therapy and administration of vasoactive drugs to maintain vital organ perfusion and oxygen delivery is mandatory. Understanding the different approaches in the management of critically ill patients during the resuscitation and further management is essential to initiate adequate context- and time-specific interventions. Treatment of hemodynamic variables to achieve a balance between organ oxygen delivery and consumption is the cornerstone. In general, cardiac output is considered a major determinant of oxygen supply and thus its monitoring is regarded helpful. However, indicators of oxygen requirements are equally necessary to assess adequacy of oxygen supply. Currently, more and more less or even totally non-invasive monitoring systems have been developed and clinically introduced, but require validation in this particular patient population. Cardiac output monitors and surrogates of organ oxygenation only enable to adequately guide management, as patient’s outcome is determined by acquisition and interpretation of accurate data, and finally suitable management decisions. This mini-review presents the currently available techniques in the field of hemodynamic monitoring in critically ill patients and briefly summarizes their advantages and limitations.